THE EFFECT OF WORK MOTIVATION AND WORK ENVIRONMENT ON PERFORMANCE WITH SATISFACTION AS INTERVENING VARIABLES EDUCATION PERSONNEL REKTORATE ANDALAS UNIVERSITY - ., Dafruddin; Heryanto, Heryanto (Archives of Business Research, 2019)
This study aims to obtain empirical evidence regarding the effect of work motivation and work environment on performance with satisfaction as an intervening variable of unand rectorate education staff. The population in this study were all unand rectorate education staff totaling 351 people. The technique used in sampling is to use the census method, wich is 187 people. The type of research used is descriptive quantitative.The analysis shows that work motivation has a positive and significant effect on satisfaction of the Unand Rectorate education staff, indicated by significance values t, which equals to 0.001 smaller than α = 0.05 (0.001 <0.05) with a regression coefficient of 0.206. The work environment has a positive and significant effect on employee satisfaction of Unand rectorate education staff, which is indicated by a significance value t of 0,000 smaller than α = 0.05 (0,000 <0,05) with a regression coefficient of 0,374. Motivation work has a positive and significant effect on the performance of Unand rectorate education staff, indicated by a significance value of t of 0,000 smaller than α = 0.05(0,000 <0, 05) with a regression coefficient of 0,319. Work environment is positively and significantly influencial to the performance of the Unand rectorate's education staff, indicated by a significant value t of 0.023 smaller than α = 0.05 (0.023 <0.05) with a regression coefficient of 0.166. Job satisfaction has a positive and significant effect to the performance of the UNAND Rectorate education staff, indicated by the significance value of t is 0,000 smaller than α = 0,05 (0,000 <0,05) with the coefficient regression of 0.390.